Ventriculosubgaleal shunting in the treatment of posthemorrhagic hydrocephalus of premature infants: case series - Alexandre Canheu (Brazilian Society for Pediatric Neurosurgery, 2021)
Introduction: Posthemorrhagic hydrocephalus(PHH) comprises the most common complication in preterm infants (PTI) who suffered germinative matrix hemorrhage (GMH), and its treatment is still matter of controversies. These infants usually weigh less than 1,500g and a temporary CSF diversion is needed. VSGS is preferred in those cases because it is a simple and rapid method, no need for repetitive aspiration for the evacuation of CSF, gives a permanent decompression without causing electrolyte and nutritional losses, and still protects the cerebral development of newborns with GMH. Methods: We analyzed a series of 22 PTI who underwent VSGS for PHH, between July 2015 and April 2019, and minimum follow-up 6 months. The median gestation age was 28 weeks (range 23-32). The median weigh was 985g (range 625-1615). The mean period harboring de VSGS was 61,8 days (range 35-80). Results: The cases were studied for: 1) Shunt dependency: 11 children (50%) showed persistent hydrocephalus at further investigation and underwent to VP shunt after stable clinical condition. 2) Infection: 6 subjects (27,2%) showed positive cultures, and were converted to External Ventricular Device (EVD), and further VP shunt; 3) Outcome: the results were separated in Excellent/Good (GOS 5-4) 12 subjects (54%); Poor (GOS 3-2): 8 subjects (36%) and Death (GOS 1): 2 subjects (10%). Conclusions: VSGS is a good alternative method to treat PHH, especially in a preterm infant who needs a temporary shunt device. The low rate of severe complications and encouraging results about persistent hydrocephalus should guide further investigation and larger cases series.